2019
DOI: 10.1175/jhm-d-18-0141.1
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term and Long-Term Surface Soil Moisture Memory Time Scales Are Spatially Anticorrelated at Global Scales

Abstract: Land–atmosphere feedbacks occurring on daily to weekly time scales can magnify the intensity and duration of extreme weather events, such as droughts, heat waves, and convective storms. For such feedbacks to occur, the coupled land–atmosphere system must exhibit sufficient memory of soil moisture anomalies associated with the extreme event. The soil moisture autocorrelation e-folding time scale has been used previously to estimate soil moisture memory. However, the theoretical basis for this metric (i.e., that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 60 publications
5
73
0
Order By: Relevance
“…In contrast, ∆S in humid river basins is mostly controlled by changes in groundwater, followed by changes in soil moisture. These results are well supported by the literatures, since the response of groundwater fluxes to climate variability in arid regions is weaker than that in humid regions [Cuthbert et al, 2019], and the soil moisture memories (defined as the time taken to dissipate an anomaly) in humid regions are longer than those in arid regions [McColl et al, 2019]. Rahman et al [2015] also illustrates that the soil moisture memory timescale showed an exponential relationship with the basin aridity index, which is in line with our results that SM changes displayed an exponential relationship with the variable moisture conditions.…”
Section: Accepted Articlesupporting
confidence: 88%
“…In contrast, ∆S in humid river basins is mostly controlled by changes in groundwater, followed by changes in soil moisture. These results are well supported by the literatures, since the response of groundwater fluxes to climate variability in arid regions is weaker than that in humid regions [Cuthbert et al, 2019], and the soil moisture memories (defined as the time taken to dissipate an anomaly) in humid regions are longer than those in arid regions [McColl et al, 2019]. Rahman et al [2015] also illustrates that the soil moisture memory timescale showed an exponential relationship with the basin aridity index, which is in line with our results that SM changes displayed an exponential relationship with the variable moisture conditions.…”
Section: Accepted Articlesupporting
confidence: 88%
“…(5) and (6) imply that anomalies in runoff and infiltration are generally large for a given P 0 . Higher runoff and infiltration fluxes in wet regions have been inferred from satellite observations of soil moisture (McColl et al 2019) and in soil chamber experiments dating back to the earliest examinations of flow through porous media (Richards 1928). In dry regions where s(P ) is generally small, Eqs.…”
Section: A Linear Response Surface Fluxesmentioning
confidence: 99%
“…Orth and Seneviratne (2013) used data from >100 catchments across Europe to study the impact of SWC memory (persistence characteristic) on ET a and runoff. Memory effects are typically studied using autocorrelation of observed or modeled SWC time series (McColl, He, Lu, & Entekhabi, 2019). Orth and Seneviratne (2013) found higher memory effects for monthly averaged data of SWC and ET than for daily averaged values, because the monthly aggregation takes out the daily variations of meteorological effects.…”
Section: Introductionmentioning
confidence: 99%